Pengaruh Edukasi Pelanggan pada Loyalitas Pelanggan melalui Kualitas Jasa - Rully Arlan Tjahyadi; Chandra Kuswoyo; Cen Lu; William Irianto (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2021)
When customers actively participate in value creation, companies develop capabilities to understand customer needs. It shows that companies and customers play an active role in creating value. Some experts suggest that the inculcation of value is essential in the co-creation process between companies and customers and that customers change from passive listeners to active players. So the value creation process must focus on developing processes to support customer learning. Customers must learn relevant skills and behaviours in the purchase, production, and use of goods or services to participate and contribute to creating value effectively. Educating customers and ensuring customer knowledge of a service is the primary determinant of service quality and customer loyalty. This study uses Path Analysis to examines customer education's effect on customer loyalty through service quality. The result shows that customer education affects customer loyalty directly or indirectly through service quality. This study's findings indicate that customer education is an essential concept in achieving competitive advantage. Customer education is understood as active customer participation to improve excellent service